TEKNO-KONOMI: BROADBAND INTERNET SEBAGAI STRATEGI PERTUMBUHAN INVESTASI DAN PENINGKATAN KESEJAHTERAAN MASYARAKAT INDONESIA - Siti Aminah Caniago; Caniago, Siti Aminah; Rozi, Feni Fitriani Putri; Wijaya, Bagaskara Sagita (STAI Syubbanul Wathon Magelang, 2022)
This study will examine the impact of using broadband internet networks on two sectors of economic growth, namely Foreign Direct Investment and the social welfare of the people in Indonesia following the provisions of the Human Development Index from the United Nations by restructuring the economic sector through the implementation of research and development, innovation, and other factors strengthen economic digitization in Indonesia and describe upgrading steps to realize economic digitization in Indonesia. Using qualitative data and descriptive analysis methods, the researchers analyzed the Internet's development, potential, and role in developing the digital economy. The observation and recapitulation system of online investment transactions, online journals, books, papers, and other publications were used to obtain data in this study. As a result of this research, the challenge of economic digitization in Indonesia is the ability of Indonesian people to adapt to new technologies and the diversity of local values in Indonesia, which are still common. The strategy that can be applied is to develop infrastructure that supports internet connections and strengthen digital economic development governance that maintains the value of Indonesian locality by involving various parties through collaborative steps. The use of the Internet will provide different economic benefits for a country, depending on the country's income level. In conclusion, the digital economy in Indonesia must improve financial processes and investment through technological innovation, Encourage growth through government regulations, and involve new actors in society as the foundation of economic growth and people's welfare.